2020
DOI: 10.1590/0034-7167-2019-0883
|View full text |Cite
|
Sign up to set email alerts
|

Effects in the development of children exposed to zika virus in the fetal period: an integrative review

Abstract: Objective: To know the evidence available in the literature on the effects of the zika virus in children development after fetal exposure. Methods: This is an integrative literature review with 16 scientific articles found in five databases (PubMed, LILACS, CINAHL, Web of Science and Scopus), based on the guiding question: “What are the effects in the development of children aged 0 to 6 years exposed to the zika virus in the fetal period? The STROBE statement was used for data extraction and evaluation of pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…In February 2016, due to outbreaks in the Pacific and mainly in the Americas, ZIKV became an international public health emergency [ 2 ]. In the recent epidemic of 2015–2016, sexual, perinatal, and blood [ 3 , 4 , 5 , 6 ] transmission was evidenced, in addition to neurological complications, serious complications compatible with congenital Zika virus syndrome (CZVS), changes in growth and development of children whose mothers were exposed during pregnancy, low birth weight, and even fetal loss [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In February 2016, due to outbreaks in the Pacific and mainly in the Americas, ZIKV became an international public health emergency [ 2 ]. In the recent epidemic of 2015–2016, sexual, perinatal, and blood [ 3 , 4 , 5 , 6 ] transmission was evidenced, in addition to neurological complications, serious complications compatible with congenital Zika virus syndrome (CZVS), changes in growth and development of children whose mothers were exposed during pregnancy, low birth weight, and even fetal loss [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A dengue na gestação está associada ao aumento do risco de perda fetal; o Zika à teratogenicidade, possui tropismo pelo Sistema Nervoso Central -SNC, podendo ocasionar complicações fetais, com efeito irreparáveis em crianças expostas no período fetal, desde a microcefalia a outras alterações no SNC (Charlier et al, 2017;Santos et al, 2020). A chikungunya na gestação pode desencadear, desde óbitos fetais, sem malformações, até o nascimento de recém-nascidos infectados, podendo desenvolver manifestações graves, como meningoencefalite e coagulação intravascular, levando à hospitalização neonatal prolongada em unidade de terapia intensiva (Torres et al, 2016).…”
Section: Introductionunclassified
“…Through these studies, brain calcifications, motor, cognitive and visual changes have been identified, these being of a neurological nature, since this virus has an affinity for the nervous system. [2][3][4] facilities. This research also covered, online, others responsible for children diagnosed with microcephaly, in addition to the HU environment.…”
Section: Introductionmentioning
confidence: 99%